Divergence Studies in Chilli Genotypes (Capsicum annuum L.) - Singh, Sakshi; Joshi, A. K.; Vikram, Amit; Kansal, Sandeep; Singh, Sudha (International Journal of Economic Plants, 2023)
A study on genetic diversity was conducted at Experimental Farm of Regional Horticultural Research and Training Station Dhaulakuan, District Sirmour (HP), Dr. YS Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India during kharif season, 2018 to assess the genetic diversity in 21 genotypes of chilli (Capsicum annuum L.) and to identify suitable donors for successful breeding programme in this crop.The twenty one (21) chilli genotypes were evaluated for seven horticultural traits viz., days to 50% flowering, days to first green fruit picking, fruit length (cm), fruit diameter (cm), number of fruits plant-1, fruit weight at edible maturity (g), green fruits yield plant-1 (g). The experiment was laid out in RCBD with three replications at spacing of 45×45 cm2. By estimating D2 values in all possible combinations of the genotypes, the 21 genotypes of chilli were grouped into 6 clusters based on green fruit characters, revealing the genetic diversity among the parents. Cluster IV had maximum (6) andCluster I with only one genotype. Average intra-cluster distance was maximum in cluster VI (19.56). The inter cluster distance was recorded maximum between cluster I and VI (207.49). Therefore, hybridization between the genotypes from cluster I and VI (green) can be utilized for getting superior recombinants/ transgressive segregants in segregating generations of chilli.